Quantifying total carbon stock of mature oil palm - Elisa Rumpang (2021)
The carbon stock of oil palm is an important indicator of environmental and agronomical impact of oil palm. Measuring variations in oil palm biomass with age, geographical region, and plantation management are necessary to accurately predict carbon stock across ecosystems. However, quantification of total carbon stock for mature oil palms is not well described. Here, we determined above- and below-ground biomass of mature palms planted on mineral soil in Sarawak, Malaysia using both destructive and non-destructive methods. Based on allometric equations, older palms constitute a greater total carbon stock, with the largest contributions from trunks and roots. Total carbon stocks assessed per the non-destructive method were 50.7 Mg C ha¯¹, 44.4 Mg C ha¯¹, and 72.1 Mg C ha¯¹ in 11-year old, 21-year old, and 29-year old palms, respectively. Our results show that trunk biomass increases with the age of palms. Root biomass was substantially higher in older palms. Using the destructive method, total carbon stock of the 21-year old palms was approximately 51.3 Mg C ha¯¹. Differences between the two methods may be attributed to unaccounted palm components using the non-destructive method. The inclusion of unaccounted palm components, such as spears, cabbage and trunk bole would increase total carbon stock of 21-year old palms to approximately 48.0 Mg C ha¯¹. This suggests that the non-destructive method may effectively estimate carbon stock, given specific corrections and assumptions. This study demonstrates a field applicable approach for quantifying the total carbon stock of oil palm to assess the impact of oil palm plantation on the ecosystem carbon balance.